Effects of packaging and duration on quality of minimally processed and unpitted litchi cv. ‘Mauritius’ under low storage temperature - Rebogile R. Mphahlele; Oluwafemi J. Caleb; Mduduzi E.K. Ngcobo (Heliyon, 2020)
Pericarp drying is a major postharvest challenge affecting the shelf life of litchi fruit resulting in loss of market value and consumer rejection. Sulphur dioxide (SO2) is considered an allergen due to its ability to cause irritation in people, particularly those vulnerable to asthma. Thus, the objective of this study was to investigate the effects of packaging and storage duration without SO2 on the quality attributes of minimally processed litchi fruit cv. ‘Mauritus’. Minimally processed litchi cv. ‘Mauritius’ were packed inside clamshell trays with different perforation sizes: 0 (P-0), 1.1 mm (P-1), and 5.4 mm (P-2) and stored at 1 °C for 15 days, and then held at 12 °C for 2 days for shelf life study (mimicking retail practices). The least mass loss % was observed in fruit packaged under P-0 followed by P-1 and P-2 until the end of storage. Fruit packed in P-2 (5.4 mm perforation) had the highest firmness compared to samples from other packages, but, they also had the highest decay incidences at day 9. The TSS (°Brix) was highest in fruit packed under P-0 followed by P-2 than P-1 at the end of storage. The TSS:TA increased significantly with storage duration with highest value obtained on day 9 in P-0 (121.63) in comparison to P-1 (108.44) and P-2 (103.35). Ascorbic acid and radical scavenging activity declined with prolonged storage irrespective of package type. Overall litchi fruit were better maintained in non-perforated and 1.1 mm perforated clamshell trays up to 9 days, without decay incidences.